Avaliação da biossorção dos íons metálicos (Cu2+, Cd2+ e Pb2+) pela biomassa de macrófitas aquáticas - Freitas, Franciele de (2018)
Aquatic macrophytes are naturally potential biosorption agents of various types of substances. This potential can be applied to the mitigation of impacts caused by the contamination of water bodies and effluents by metals. Thus, the objective of this study was to evaluate the biosorption process of metallic ions of liquid solution by the living and dry biomass of aquatic macrophytes. The study is structured in two articles. In the first article the biosorption of Cd2+ and Pb2+ ions of aqueous solution by Salvinia biloba living biomass was evaluated. The experiment was performed in BOD chambers adjusted in 12-hour photoperiod and mean temperature of 25±1°C. In all the trials the plants were conditioned in plastic containers containing 1L of aqueous solution at pH 6.5, with nutritive treatment. The kinetic assay was performed at the initial concentrations (C0) of 1.0 and 7.0 mg. L -1 for Cd2+ and Pb2+ , respectively, and the contact time (solution / plants) was between 1 and 168 hours. In the isotherm assay, the initial concentration of the metals ranged from 0.5 to 7 mg. L -1at the 72 hequilibrium (3 days) for both metals. Salvinia biloba presented biosorption potential (adsorption/absorption) of Cd2+ and Pb2+ ions in aqueous solution. Metal toxicity effects were observed in plants, mainly Cd2+ at 7.0 mg. L-1. The highest removal and tolerance efficiency was presented with Pb2+, suggesting mechanisms of resistance to this metal. Salvinia biloba can be indicated for phytoremediation of Cd2+ and Pb2+ from aquatic environments, and the 48-hour period is recommended for this purpose. In the second article the dry biomass of Eichhornia crassipes, Pontederia rotundifolia and Salvinia biloba was evaluated for the adsorption efficiency of copper ions (Cu2+) and lead (Pb2+) of aqueous solution in a batch system. The fixed variables were the biomass of 2g, the pH adjusted to 6.0, the agitation at 50 rpm and the temperature at 25°C. The characterization of the average granulometry of the materials was done by the sieving method. For the kinetic assay the initial concentration (C0) of adsorbate varied in 5, 10 and 20 mg. L-1and control (0 mg. L-1), while the contact time (adsorbent / adsorbate) was established between 0, 08 minutes (5 seconds) and 720 minutes (12 hours). In the isotherm assay the initial concentrations of Cu2+ varied between 5 and 50 mg. L-1and of Pb2+ between 1 and 20 mg. L-1 at the 120 minute equilibration time for E. crassipes and P. rotundifolia, and 240 minutes for S. biloba. The equilibrium data were adjusted to the Langmuir and Freundlich models. The adsorbents from the E. crassipes, S. biloba and P. rotundifolia biomasses have important characteristics for the adsorption of Cu2+ and Pb2+ ions, such as rapid kinetic conditions of removal, low ionic removal capacity and similar adsorption capacity adsorption adsorbents. The equilibrium data fit the Langmuir model. Among the biomasses evaluated, E. crassipes presented higher Cu2+ removal efficiency and P. rotundifolia presented the best results for Pb2+ adsorption. In general, the evaluated macrophytes are abundant and inexpensive biosorbent materials with potential for application in phytoremediation systems for the mitigation of Cu2+, Cd2+ and Pb2+ of liquid solutions.